Implementasi Program Makan Bergizi Gratis (MBG) dalam Mewujudkan Kesejahteraan Masyarakat Perspektif Maqashid Syariah - M. Firdaus Tri Kuncoro; Luluk Hanifa; Mashudi Mashudi (CV. Global Cendekia Inti, 2026)
The Free Nutritious Meals Program (MBG) is one of the Indonesian government’s strategic policies aimed at improving the population’s nutritional status, supporting educational quality, and strengthening social welfare. Although various studies have examined the program’s impact from health, educational, and economic perspectives, research that integrates the implementation of the MBG within the Maqashid Syariah framework through a Systematic Literature Review (SLR) approach remains relatively limited. This study aims to analyze the implementation of the Free Nutritious Meals Program from the perspective of Maqashid Syariah and its implications for public welfare. The study employs a Systematic Literature Review (SLR) method in accordance with the PRISMA guidelines. Literature was obtained through searches in the Google Scholar, Scopus, Crossref, and Garuda databases using predetermined keywords. After undergoing a process of identification, screening, feasibility assessment, and selection based on inclusion and exclusion criteria, 15 articles were identified and analyzed thematically. The research results indicate that the Free Nutritious Meals Program makes a positive contribution to improving nutritional status, educational quality, and community economic empowerment, while also supporting the achievement of the Maqashid al-Sharia objectives, particularly in the aspects of hifz al-nafs (protection of life), hifz al-‘aql (protection of the mind), and hifz al-mal (protection of property). However, the program’s implementation still faces various challenges, such as equitable distribution, the effectiveness of oversight, interagency coordination, and the sustainability of funding.